Methodology for International Drug Monitoring - ROYALL, B. W.; VENULET, J. (Methods of Information in Medicine, 1972)
Because of increasing evidence that the adverse effects of therapeutic drugs often present serious hazards to patients and that available knowledge and experience in this field were not considered to be sufficiently well developed to provide adequate protection against such situations in the future, WHO has been requested to undertake a feasibility study in the field of international co-operation in drug monitoring.The present paper includes (1) the exploratory activities which preceded and led to the implementation of the WHO Pilot Research Project for International Drug Monitoring, (2) the basic concept and description of methodological research and development undertaken during the pilot phase.
Keywords: Drug Monitoring; Adverse Reactions; International Pilot Project